2022
DOI: 10.1021/acs.organomet.2c00065
|View full text |Cite
|
Sign up to set email alerts
|

Ni(I) Intermediates Formed upon Activation of a Ni(II) α-Diimine Ethylene Polymerization Precatalyst with AlR3 (R = Me, Et, and iBu), AlR2Cl (R = Me, Et), and MMAO: A Comparative Study

Abstract: A variety of heterobinuclear Ni(I) complexes of the general formula [LNi I (μ-X 1 )(μ-X 2 )AlR 2 ] formed upon the activation of the [LNi II Br 2 ] (1) ethylene polymerization catalyst (L = 1,2bis [(2,6-diisopropylphenyl)imino]acenaphthene) with AlR 3 (R = Me, Et, and i Bu), AlR 2 Cl (R = Me, Et), and MMAO were detected and characterized in situ by EPR and 1 H NMR spectroscopy. The nature of the bridging groups X 1 and X 2 (X 1 , X 2 = R, Br, or Cl) depends on the nature and excess of the cocatalyst used. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…This result suggests the presence of radical anion species consisting of aluminum and a diimine ligand. Similar signals are reported in the study of the other Ni-diimine complex treated with modified MAO or trialkylaluminum. , The difference in the spectral shape at room temperature (Figure a,b) is probably because of the mobility of Ni­(I) species in solution, where the as-received MAO can move rapidly in the ESR timescale.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This result suggests the presence of radical anion species consisting of aluminum and a diimine ligand. Similar signals are reported in the study of the other Ni-diimine complex treated with modified MAO or trialkylaluminum. , The difference in the spectral shape at room temperature (Figure a,b) is probably because of the mobility of Ni­(I) species in solution, where the as-received MAO can move rapidly in the ESR timescale.…”
Section: Resultssupporting
confidence: 80%
“…The total spin was increased at the frozen state (1.8 × 10 −3 M in 2/as-Scheme 2. Activation Mechanism of Ni(II)-Diimine Complex 2 48,55 The difference in the spectral shape at room temperature (Figure 3a,b) is probably because of the mobility of Ni(I) species in solution, where the as-received MAO can move rapidly in the ESR timescale. The UV−vis and ESR measurements have revealed that MAO does not affect the electronic property of the Ni(I) resting state, suggesting that the electronic property of Ni(II) active species is not affected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The formation of Ni(I) species during the activation of nickel α-diimine complexes with aluminium activators (like MAO, MMAO and alkylaluminium species) has been repeatedly mentioned in the literature. [29][30][31][32] To follow and understand the SiHB activation processes associated with the oxidation state changes of the nickel center, EPR experiments using three hydrosilanes were performed. The detailed experimental setup and conditions are described in the ESI.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Recently, Soshnikov et al have shown that α-diimine Ni(II) complexes under the action of R 2 AlCl form the Ni(I) complex Ni07 with Ni–(μ-Cl)–Al fragments, representing the catalyst’s resting states [ 277 ]. It is quite possible that derivatives of similar species are essential to ensuring ‘living’ ethylene/α-olefin copolymerization with the formation of block -polyolefins [ 280 ].…”
Section: Complexes Of Nimentioning
confidence: 99%
“… Structural formula of Ni pre-catalysts studied in α-olefin oligomerization and polymerization: ( a ) Ni02 [ 272 ] ; ( b ) Ni03 [ 273 ]; ( c ) Ni04 [ 274 ]; ( d ) Ni05 [ 275 ]; ( e ) Ni06 [ 276 ] ; and ( f ) Ni07 [ 277 ]. …”
Section: Figures Schemes and Tablementioning
confidence: 99%